The Glottal Stop in English: A Descriptive Study (Journal of the College of Basic Education, 2022)
This study provides a descriptive account of the glottal stop in English.The glottal stop is a speech sound made by closing and opening the glottis which in English sometimes takes the place of /t/ as in water for example. It is said that the glottal stop is difficult in pronunciation and recognition for foreign learner of English. However, it is used to conform many functions. The present study tries to explore these functions and the contexts in which it may appear. In addition to that it investigates the actual status of this sound, i.e. whether it is considered a phoneme or not in the English language. Thus, this study tries to provide a thorough description of the glottal stop and other related phenomena in British English and American English. The results of this study can be briefly outlined in the following points: